Avaliação de maltes modificados nas características da clarificação da cerveja - Benavide, Lucas (2025)
Visual quality is one of the main criteria evaluated by beer consumers, who generally seek a clear beer. The use of commercial clarifiers in beers has become a common practice in the brewing industry, with the aim of improving the appearance of the product, removing suspended particles and turbidity. Despite their effectiveness, the use of these clarifiers can present some disadvantages, altering the flavor, aroma and texture of the beverage. Therefore, although commercial clarifiers play an important role in beer production, their negative impacts cannot be overlooked, and it is essential that brewers consider alternatives to the clarification process, ensuring a higher quality beverage that is more in line with the expectations of conscious consumers. Modified malts, as beer clarifiers, have gained attention in the brewing industry as a more natural and less invasive alternative to traditional commercial clarifiers, such as gelatin and bentonite. Thus, the objective of this study was to develop modified malt for craft beer production with the purpose of creating a new product to be an alternative to commercial clarifiers. For this purpose, modified malts of types A, B and C were produced, followed by the production of five standardized beers: white, control, beer with modified malt A, B and C. Subsequently, physicochemical analyses were performed during the maturation phase, namely total proteins, phenolic compounds, turbidity and clarity. Afterwards, the beer with modified malt that performed best in the previous analyses was selected to proceed to the sensory analysis. As a result, it was found that the beers with modified malts presented positive results in relation to beer clarification, which attested to reductions of approximately 66% and 83% in turbidity and clarity, respectively. In the sensory evaluation, the beer with modified malt was well accepted by the evaluators in relation to turbidity and color. Regarding flavor and bitterness, there was no sensory difference compared to the white and control, suggesting that the beer with modified malt did not alter these attributes. Finally, this study presented consistent results of the possible application of modified malts during beer production, promoting clarifying advantages to the final product.